Konselor sebaya di sekolah: Upaya penanganan masalah pada Siswa SMK Telkom Makassar - Abdul Saman; Syamsul Bachri Thalib; Muhammad Ilham Bakhtiar (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The aim of this activity is to provide training aboutpeer counsellors and to form a school peer counsellorcommunity. The activity was carried out in the form oftraining with lecture methods, counselling practices, andsimulations. This training involved 36 representative studentsfrom each class. The material provided starts from the basicconcept of peer counsellors, problems and how to handle themand basic counselling techniques followed by counsellingpractice. The results of this activity showed that the peercounsellor training activities in SMK Telkom Makassar havebeen carried out well with the results of the evaluation scorewas in a very good category, meaning that students understandwell the presented materials such as Basic concepts of PeerCounsellors that discuss the meaning, role, objectives,principles of peer counsellors as well as the requirements to bepeer counsellors and issues and prevention and finally basiccounselling techniques, which aims to equip participants toknow the basic types of counselling techniques and can beapplied later which ends the counselling practice. Then a peercounsellor has been established in SMK Telkom Makassarwhere the members are the representatives of grade X gradeXI. The established peer counsellors will become thecounsellor agents who help their counselling teachers run theguidance and counselling services at school.